International Policy Coordination and Simple Monetary Policy Rules - Berger, Wolfram (IMF Working Papers; Working Paper ;, 2006)
This paper studies the optimal design of monetary policy in an optimizing two-country sticky price model. We suppose that the production sequence of final consumption goods stretches across both countries and is associated with vertical trade. Prices of final consumption goods are sticky in the consumer's currency. Pursuing an inward-looking policy, as suggested in recent work, is not optimal in this set-up. We also ask which simple, id est non-optimal, targeting rule best supports the welfare maximizing policy. The results hinge critically on the degree of price flexibility and the relative importance of cost-push and productivity shocks. In many cases, a strict targeting of price indices like producer or consumer price indices is dominated by rules that allow for some fluctuations in prices such as nominal income or monetary targeting.